Laser organic crystals: anthracene - Valera Palacios, Aníbal (2009)
In this contribution are shown organic crystals obtained by the sublimation method and the latest experimental results obtained with the Anthracene monocrystals: A) Luminescence at room temperature. The Anthracene crystals were subjected to frontal UV-Vis irradiance, obtaining the frontal transmittance and the edge Fluorescence (wave guide emission) at room temperature. As a result of this measurements we identified a “quasigap” of 3.11eV (398 nm) and emission bands in 3.08, 2.92, 2.79 and 2.61 eV. B) Photovoltaic conversion. We constructed photovoltaic junctions Anthracene / Tin oxide (Ant / TO). We determined experimentally the quantum spectral efficiency of the system and the corresponding theoretical band energy diagram.